Polish Medical Migrants in the United Kingdom: The Complicated Nature of Their Belonging to a New Society - Ślęzak, Ewa (Lidé města, 2014)
The paper aims at analyzing the effects induced by processes of migration of Polish medical professionals to the United Kingdom following Poland´s accession to the European Union and their situation in the UK. First, a brief note on the methodology and characteristics of the sample is presented. Second, migration of Polish medical professionals is juxtaposed to existing migration theories. Third, belonging and integration are introduced, to be followed by some striking observations related to Polish medical migrants in the UK. Migrants share their opinions of the receiving society and of their lives in Poland and the UK.